2019
DOI: 10.7150/jca.32875
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine inhibits the migration and invasion of hepatocellular carcinoma cells by reducing the activity of MMP-2/-9 via regulating p38 signaling pathway

Abstract: As one of the major alkaloid components in Sophoraflavescensait (kushen), oxymatrine has been used widely across the world in anti-inflammatory and anti-cancer therapies. However, the effect in the metastasis of hepatocellular carcinoma (HCC) and related mechanism(s) are still unclear. The present study aimed to investigate the anti-metastatic effect of oxymatrine on HCC cells. Oxymatrine could also inhibit the protein levels of MMP-2/-9 in a dose-dependent relationship. Moreover, oxymatrine reduces the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Matrine could suppress the BrCSCs (breast cancer stem cells) differentiation and self-renewal by downregulating Lin28A expression, leading to the inactivation of Wnt pathway in a Let-7b-dependent way ( Li et al, 2020 ). Oxymatrine could inhibit the invasiveness of HCC by reducing the expression of MMP-2/-9 via inhibiting the activity of p38 signaling pathway ( Chen et al, 2019 ). Meanwhile, Smilacis Glabrae Rhixoma has also been reported to have anti-inflammatory, antiviral, anti-cancer, and immunomodulatory effects ( Jiang and Xu, 2003 ; Ooi et al, 2004 ; Galhena et al, 2012 ; Samarakoon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Matrine could suppress the BrCSCs (breast cancer stem cells) differentiation and self-renewal by downregulating Lin28A expression, leading to the inactivation of Wnt pathway in a Let-7b-dependent way ( Li et al, 2020 ). Oxymatrine could inhibit the invasiveness of HCC by reducing the expression of MMP-2/-9 via inhibiting the activity of p38 signaling pathway ( Chen et al, 2019 ). Meanwhile, Smilacis Glabrae Rhixoma has also been reported to have anti-inflammatory, antiviral, anti-cancer, and immunomodulatory effects ( Jiang and Xu, 2003 ; Ooi et al, 2004 ; Galhena et al, 2012 ; Samarakoon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the understanding of oxymatrine on metastasis is rarely elucidated. Chen et al 28 reported oxymatrine can block the metastasis of hepatocellular carcinoma cells in vitro by reducing p38-mediated MMP-2/-9 expression. Here, not only oxymatrine inhibition of metastasis in colorectal cancer cells, but also the molecular mechanism was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…As overexpression of p38 can increase MMP-9-dependent invasion of pancreatic cells, p38 is one of the target molecules to ameliorate PC [7]. Natural compounds, including silibinin and oxymatrine, have inhibitory effect on MMP-2 and MMP-9 via p38 inactivation in gastric and pancreatic cancer cells [35,36]. In our study, AGE and its effective compound decursin inhibited activation of MMPs by decreasing p38 phosphorylation in PANC-1 and MIA PaCa-2 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%